A prática do canto coral juvenil como recurso integrador para o ensino técnico em música - CARNEIRO, Vinícius Inácio (2011)
The present study investigates the curriculum integration aspects provided by youth choir practice, as a curricular component in the study of music at the technical (High School) level. The starting point was the course program of the discipline Choral Singing, in the Technical Course in Instrument at the Goias Federal Institute (IFG), class of 2010, as it related to the rest of the program. This investigation was based upon the evaluation of applied questionnaires, as well as upon the artistic results obtained. The investigation is to be guided by evaluation of questionnaires during the search. Part of this work is dedicated to report the author's experience as a conductor of the IFG, with emphasis on the occurrence of curriculum integration elements throughout. It was possible to verify that the curriculum integration, still occurs in a partial manner at the above mentioned institution. Therefore, the full potential of this integration has not been achieved as yet.